Clonal Propagation of Flacourtia indica for Ensuring Quality Planting Materials and Sustainable Supply of Edible Fruits - Md. Alamgir Kabir; Md. Hasan Mehedi Khan; Md. Masudur Rahman; A.T.M. Rabiul Alam; S.M. Hemayet Jahan; A.K.M. Mostafa Zaman; Muhammad Zahid Al Mamun (International Journal of Agriculture System, 2017)
The present study was carried out at the Agriculture research field, Patuakhali Science And Technology University(PSTU), Patuakhali, from March, 2015 to April, 2016 to explore the domestication potential and to evaluate the rooting performance of Flacourtia indica (katabohori), a wild fruit species in Bangladesh, through clonal propagation by stem cutting under 3 different doses of rooting hormone IBA (Indole Buetaric Acid) and planted in the perforated plastic tray filled with coarse sand and gravel placed in the non-mist propagator. The experiment was laid out following a Randomized Complete Block Design (RCBD) with 4 treatments and 4 replications (blocks). The treatments were T0= control, T1 = 0.2% IBA, T2 = 0.4% IBA, T3 = 0.8% IBA. The rooting ability of cuttings was significantly influenced by the application of IBA. The results showed that the highest rooting percentage (100) and maximum root number (8) of Flacourtia indica stem cuttings were obtained from the cuttings treated with 0.4% IBA followed by 0.2% IBA where as the longest root length (8.998 cm) was recorded with 0.2% IBA followed by 0.4% IBA. Survival percentage of the cutlings (the rooted cuttings) after 3 months of transferring them into poly bags was also significantly enhanced by exogenous rooting hormone (IBA) application. The highest survival percentage (84.5 %) was for the cuttings treated with 0.4% IBA followed by 0.2% IBA (71%). The similar trend was also observed for average cutling height and number of leaf. Findings of the present study reveal that the plant species is highly amenable for clonal propagation by stem cuttings using low-cost non-mist propagator. Considering both rooting percentage and root number, 0.4% IBA treatment of stem cuttings may be recommended for mass production of quality planting stocks for the domestication of the species in homestead agroforestry or in fruit orchards to provide edible fruit to rural poor people of natural disaster vulnerable Bangladesh.